2017
DOI: 10.1063/1.4986872
|View full text |Cite
|
Sign up to set email alerts
|

On-chip cell analysis platform: Implementation of contact fluorescence microscopy in microfluidic chips

Abstract: Although fluorescence microscopy is the gold standard tool for biomedical research and clinical applications, their use beyond well-established laboratory infrastructures remains limited. The present study investigated a novel on-chip cell analysis platform based on contact fluorescence microscopy and microfluidics. Combined use of a contact fluorescence imager based on complementary metal-oxide semiconductor technology and an ultra-thin glass bottom microfluidic chip enabled both to observe living cells with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…Such systems have been demonstrated to resolve highly comparable fluorescent images of live cells [ 102 – 104 ] (Fig. 9 ).…”
Section: Future Outlook: Contact Cmos Fluorescence Imagermentioning
confidence: 99%
“…Such systems have been demonstrated to resolve highly comparable fluorescent images of live cells [ 102 – 104 ] (Fig. 9 ).…”
Section: Future Outlook: Contact Cmos Fluorescence Imagermentioning
confidence: 99%
“…A nicer alternative would be on-chip fluorescence microscopy. 4,8,17,18 Huang et al 17 demonstrated on-chip detection of targeted oligo-DNA (21-bp) binding using Qdot-655 fluorophores with detection limits down to ∼ 20 fluorophores/µm 2 for a 50 × 50 µm pixel size in 2009. Better performance is expected now, with detection limits down to ∼ 1 fluorophore/µm 2 predicted.…”
Section: Look At the Pretty Lightsmentioning
confidence: 99%
“…24 Hence the final device structure (Fig. 1f) would be: (from bottom) CMOS backplane, 8 thin glass floor, 8 PMMA nanochannel layer, 7 polycarbonate membrane, 5 and microfluidics layers. 9 7.…”
Section: Look At the Pretty Lightsmentioning
confidence: 99%
“…Development of fluorescence and image-based single cell technologies has enabled systematic investigation of cellular heterogeneity in a wide range of diseased tissues and cellular populations [1, 2]. While conventional single cell analytical tools like flow cytometry (and Fluorescence Activated Cell Sorting, Image Flow Cytometry) can detect, sort and collect cells with desired properties, these techniques do not permit dynamic monitoring of cell responses as the data is collected at a single time point [3].…”
Section: Introductionmentioning
confidence: 99%